Jarak Optimum Panci Terhadap Selubung Pada Efisiensi Sistem Pemanasan Air - Widodo, Agung Sugeng (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2015)
Energy conservation from fossil fuel is urging to be implemented recently, including conservation in a conventional gas stove (CGS). Considering the mechanism of a CGS, there are many prospects to enhance its performance. In this study, efficiency of a CGS has been investigated by varying the gap between pan and stove cover. Many parameters were measured as energy from fuel, cover temperature and water temperature to develop efficiency equation of heating system. Ceramic cover was used to prevent heat release from flame. Gaps between pan and stove cover were varied in 1 mm to 7 mm with increment of 1 mm. The results showed that in certain fuel rate of 45 l/h, the gap of 4 mm indicated the highest efficiency of 46.4 % due to the optimum condition was achieved simultaneous in convection and radiation heat transfer processes of the heating system.